If it's not what You are looking for type in the equation solver your own equation and let us solve it.
144=6x+3(4x+12)
We move all terms to the left:
144-(6x+3(4x+12))=0
We calculate terms in parentheses: -(6x+3(4x+12)), so:We get rid of parentheses
6x+3(4x+12)
We multiply parentheses
6x+12x+36
We add all the numbers together, and all the variables
18x+36
Back to the equation:
-(18x+36)
-18x-36+144=0
We add all the numbers together, and all the variables
-18x+108=0
We move all terms containing x to the left, all other terms to the right
-18x=-108
x=-108/-18
x=+6
| 6(3y-4)-22=3(4y-5)-15 | | 144=6x+3(4x+13) | | r=-30-46 | | 3/4x-1/2=1/2x+3 | | 8-4s=2+13 | | 144=6x+3(4x+13 | | 2×+y=11 | | 70-(2x+5)=3× | | 512=f+173 | | (g+6)=3 | | 3x=642 | | 36(16-2.5x)=13(2x-10)+56.4 | | 6x-3x+15=30 | | W^2–14w+13=0 | | 9+y=42 | | 5(x+7)=6(-5) | | (y)+3=7 | | 39-5p=7(-2p+8)-8p | | 12(6+x)=8(5+x) | | 39-5p=79-2P+80-8p | | 12(6+x)=8(x+12£ | | 8(x+9)=12(x-5) | | A+31=a+1 | | -134q+8;q=8 | | 4(x-5)=18- | | 1-3k=2-2k | | 10=7–6m | | 10=7–6m | | 3-y/3=-1 | | 10(x+5)=10(x+10) | | -2(x+7)=6(x-5) | | 10(x-5)=10(x+10) |